The Role of Quality Human Resources in Developing Missions of Future Universities in Indonesian Higher Education - Ahmad Muktamar B; Ni Luh Kardini; Aria Elshifa; Susi Adiawaty; Tri Cicik Wijayanti (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
The unique human resource governance role has significantly contributed to achieving the University's mission and vision. We have carried out this study to prove the role of quality human resources in achieving the University's mission. The phenomenological approach involves, among other things, a data coding system, in-depth evaluation, high integration, and concluding the principles of validity and reliability. Context of higher education from the 15 publications we reviewed and backed up by other findings in the context of the role of HR and achieving university goals in higher education studies was resulting of this study. These findings will be helpful in the development of similar studies in the future.